The Influence of Accountability in Village Fund Allocation Management and Village Policy on Improving Community Welfare (Case Study of Bonto Tangnga Village, Bontotiro District, Bulukumba Regency) - A. Nurfadilla (Mustard Journal De Ecobusin, 2024)
The current research will endeavor to determine the role of accountability in village fund distribution and village policy in augmenting community welfare. The design of this study is the quantitative model, and the sample consists of 83 interviewees. Primary data were gathered through the use of questionnaires. The analysis of data was done using the multiple linear regression, which was done in SPSS version 25. Results show that the accountability variable related to the management of village fund allocation has a strong influence on welfare of the community just like the village policy variable; therefore, all hypotheses put forward in the research were approved and accepted.